Modern Weights and Measures Regulation in the United States : A Brief History. - Leisy, Craig A. ([Place of publication not identified] : Routledge, 2021)
In this book, Craig A. Leisy provides a concise history of weights and measures regulation in the United States from the early 20th century up to the present day. Written for academic and professional readers, Leisy describes basic terms and concepts, the origins and history of weights and measures laws, weights and measures regulation, the economics of regulation, key enforcement cases, landmark legal decisions, the effects of public policy, and a forecast on the future of weights and measures regulation. He also discusses the impact of weights and measures regulation on both producers (sellers) and consumers (buyers) in the marketplace. The book also features a new 2019 survey of state weights and measures regulatory programs, an introduction to the economics of weights and measures regulation, a case study of the municipal weights and measures regulatory program in Seattle, Washington, details of a major gasoline dispenser fraud case in Los Angeles County, and landmark legal cases related to net contents of packaged goods. Modern Weights and Measures Regulation in the United States is the only book on this subject from the perspective of a former long-time weights and measures regulatory official.
Introduction1. Modern Weights and Measures Regulation in the U.S.2. The Economics of Weights and Measures Regulation in the U. S.3. Case History: Weights and Measures Regulation in Seattle4. The National Institute of Standards and Technology (NIST) and National Conference on Weights and Measures (NCWM)5. Enforcement Issues6. Landmark Legal Cases7. Conclusions and ForecastsGlossaryAppendices
OCLC-licensed vendor bibliographic record.
Keywords: Weights and measures -- United States -- History; POLITICAL SCIENCE / Public Affairs & Administration; SOCIAL SCIENCE / General